Lived Experiences Of Adolescent Mothers Attending Mbale Regional Referral Hospital: A Phenomenological Study - Chemutai, Violet; Nteziyaremye, Julius Goodwill; Wandabwa, Gabriel Julius (Obstetrics and gynecology international, 2020)
Adolescence is a period of transition from childhood to adulthood and is thus a critical in ones’ development characterized by opportunities and risks. By 2016, 16% of the World’s population was of adolescents with 82% residing in developing countries. About 12million births are due to 15-19 year olds. Sub-Saharan Africa particularly East Africa has high adolescent pregnancy rates with ranges as high as 35.8% in Eastern Uganda. Of Uganda’s maternal mortality ratio of 336/100.000 live births, 17.1% were attributable to adolescents aged 15-19 years. Whereas research is awash with contributing factors to such pregnancies, little is known about their lived experiences during early motherhood. We therefore set to study the lived experiences of adolescent mothers attending our hospital.
Keywords: Adolescent Mothers